Factors Analysis Influencing Performance Learn Paud Town of Bengkulu - Samsul Akmal (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose this research to analyse factors influencing performance learn PAUD Town of Bengkulu, Human resource represent to have an effect on to organizational effort in reaching the target of by moving forward technology, growth of information. While management represent process how to guide, instructing group or people in organization to reach target which have been planned previously. Method analyse data collecting which used in this research is kuesioner, while method analyse is qualitative, quantitative and analyzer of scale of likert. Three factor influencing performance learn PAUD Town of Bengkulu PAUD Auladuna Town of Bengkulu, individual variable, organizational variable, psychological variable. most dominant factor influence performance learn PAUD psychological variable get perception of responder with criterion very agree. while factor both of individual variable get perception of responder with its criterion individual variable him influence performance learn PAUD Town of Bengkulu, dominant factor which is low that is organizational variable that is reward but still get perception of responder with criterion agree.